FENOMENA KOMUNIKASI PERNIKAHAN SUAMI ISTRI DENGAN PERBEDAAN TINGKAT PENGHASILAN (Studi pada Penghasilan Istri Lebih Besar dari Suami di Kota Pekanbaru) - Abrar, Zuwita; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Rampant divorce cases in marriage. Many reasons underlying the decision of divorce be one way out of the settlement of the problems faced. Moreover, in the marriage relationship where the husband and wife both work, and when the wife's income is greater than her husband, the conflict will be more frequent. Not infrequently it helped trigger their feelings of discomfort couples. Besides the many cases of divorce marriage more income that led to divorce, not a few couples who maintain a marriage relationship lived remains a lasting and happy. This study aims to reveal different motives income married couples maintain marriage relationship, the meaning of marriage relationship lived and uncover the communication experience different income couples in the city of Pekanbaru.This study uses qualitative research with phenomenological approach. Subjects were 3 couples in the city of Pekanbaru different income categories are determined based on the method of purposive then obtained using the snowball technique. The collection of data obtained through in-depth interviews, observation (observation) and literature.The results of this study indicate that the motive is different income married couples stick with their marital relationship consists of a motive for (Because motive) namely religion, character spouses, children, favors fought together and the principle of marriage. While the motive for (in order to motive) namely households established, lasting and happy, as well as weddings sakinah mawaddah warahmah. Meanings given by married couples, namely on the basis of love and faith in God the almighty One, the belief has been arranged sustenance Allah, arises a sense of pride and gratitude husband to wife and helped the role of husband. As for the communication experience categorized into two: the fun as arises a sense of belonging is high, their attitudes reinforce each other, a good reception from the family and get along with the surrounding environment and the unpleasant experience as wives often feel fatigue play two roles, the husband tends relax with a job, a family and a poor response doubts surrounding environmentKeyword: marriage, husband wife, different level of income, phenomenon of communiacation